Spontaneous Subcapsular Hematoma from Rivaroxaban - Swetha Chenna; Amy R Hurst; Jason B Douglas; Venu Madhav Chippa; Matthew R Fulton; Amr Moussa (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2018)
Rivaroxaban was approved for stroke prevention for non-valvular atrial fibrillation in 2011, with added advantage of decreased risk of bleeding in comparison to coumadin, made it a good alternative for coumadin. We report a case of severe subcapsular and intrarenal hematoma associated with Rivaroxaban in an elderly male with chronic kidney disease. He presented with severe left sided flank pain, shock and acute on chronic renal failure, he was successfully resuscitated with supportive care. We aim to alert primary care physicians, hospitalists, Emergency room physicians and cardiologists regarding the likelihood of encountering similar cases as the indications of direct acting oral anticoagulants are increasing and gaining more popularity in physicians and patients as well.